Produção, caracterização e avaliação da degradação de compósitos poliméricos incorporados com lipase e estruturas metalorgânicas - Castro, Michael da Conceicao de (2024)
Plastics and polymeric materials derived from fossil fuels have become an environmental problem due to their poor management and long degradation times. Therefore, the need to replace these materials with others from natural, bio-based or biodegradable sources has become urgent. Studying degradation models of these polymers by incorporating materials that aim to accelerate the degradation of these compounds can help solve the pollution problem and extend to studies with nonbiodegradable polymers. The use of biodegradable polyesters has been investigated on an industrial scale because they have ester bonds that can be hydrolyzed. The main objective of this work was to develop polymeric composites based on poly(butylene adipate-co-terephthalate) (PBAT) and thermoplastic starch (TPS), incorporated with Burkholderia lata lipase (BLL) and Fe-BDC metal-organic frameworks (MOFs), and to verify the degradation by composting of these composites. The lipase was added in free (BLL) and immobilized (BLL@BDC) form with the same amount of activity units. The lipase was immobilized in Fe-BDC MOF simultaneously by adsorption and encapsulation. Stability studies of BLL@BDC at temperature (20 to 150 °C, up to 1 h) and pH (2.5 to 10, 1 h) were performed before incorporation into the composites. It was observed that BLL@BDC presented residual activity of 62.73 ± 5.03, 53.79 ± 6.46 and 43.28 ± 2.02% (120 °C) for 5, 8 and 10 min and residual activity of 125 ± 8.36% at pH 4. Four types of composites were produced by extrusion and injection, POL (control), which consists of the combination of PBAT/TPS polymers. These two polymers are present in the proportion of 240:200 g in all composites produced. For the others, 21 g of lyophilized lipase (POL-BLL), 5 g of BDC (POL-BDC) and 5 g of BLL@BDC (POLBLL@BDC) were incorporated. The lowest density was for POL-BDC (2.25 ± 1.6 g cm-3) and the highest for POL (3.43 ± 0.12 g cm-3). The weight loss in water (WWL) ranged from 10.75 ± 1.00% (POL) to 50.90 ± 0.84% (POL-BDC). The incorporation of Fe-BDC caused a 57% reduction in the load-bearing capacity and 68.5% in the elastic capacity of the material, when compared to the control material. Color analysis showed that the POL-BDC and POL-BLL@BDC composites presented a color change significantly visible to the human eye. After composting, the composites underwent color changes and mass reduction, with the composite incorporating FeBDC presenting approximately 64% mass reduction in the period of 68 days, which confirms the increase in material degradation compared to the control material. The compost (substrate present in the composting windrows) meets the parameters established by Normative Instruction No. 61/2020 of MAPA, ensuring safety for use in agriculture and protecting human and animal health and the environment.